2021
DOI: 10.7717/peerj.12552
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and lethality by SARS-CoV-2 in indigenous populations of Latin America and the Caribbean: a systematic review

Abstract: Background Latin America and the Caribbean (LAC) has presented some of the highest numbers of cases and deaths due to COVID-19 in the world. Even though indigenous communities represent 8% of the total population in this region, the impact of COVID-19 on this historically vulnerable population has only been briefly explored. Thus, this study aimed to estimate the seroprevalence and lethality attributable to SARS-CoV-2 in the indigenous population of LAC. Methods A systematic review was conducted utilizing mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Similarly, the indigenous populations in LAC have had struggles with vaccination, mainly due to poor access to immunisation services [ 99 , 100 ]. High seroprevalence and lethality due to SARS‐CoV‐2 has been found in this vulnerable population [ 101 ]. Governments have been called to consider the difficult logistical challenges with the provision of vaccines in remote areas, like the Amazon jungle [ 100 ].…”
Section: Vaccinationmentioning
confidence: 99%
“…Similarly, the indigenous populations in LAC have had struggles with vaccination, mainly due to poor access to immunisation services [ 99 , 100 ]. High seroprevalence and lethality due to SARS‐CoV‐2 has been found in this vulnerable population [ 101 ]. Governments have been called to consider the difficult logistical challenges with the provision of vaccines in remote areas, like the Amazon jungle [ 100 ].…”
Section: Vaccinationmentioning
confidence: 99%
“…A meta-analysis of seroprevalence studies carried out in various countries around the world showed that by 2020, seroprevalence was low in the general population (median 4.5%, IQR 2.4-8.4%). [2][3][4] Most seroprevalence studies have been performed for convenience in urban populations. The objective of this study was to evaluate the seroprevalence of rural agricultural workers in Guatemala, the vaccination coverage against COVID-19, and the level of hesitancy and perception of these workers to vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Numerous seroprevalence studies have been conducted in the Latin American region, both population-based studies and studies focusing on specific populations (healthcare (HCW) or first-line workers, prison workers, indigenous populations, elderly populations, etc). [4][5][6][7][8][9][10][11][12][13][14][15] The reported seroprevalence is highly heterogenous between studies (10,4% -68,1 %), varying by study population, characteristics of the COVID-19 epidemic at the time of sampling, and differences in sociodemographic factors. [4][5][6][7][8][9][10][11][12][13][14][15] Factors associated with increasing risk of seropositivity include ethnicity (indigenous or Afro-descent), presence of COVID-19 symptoms, past history of COVID-19 or close contacts, lower educational level, and working night shifts (for HCW) or in a prison.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15] The reported seroprevalence is highly heterogenous between studies (10,4% -68,1 %), varying by study population, characteristics of the COVID-19 epidemic at the time of sampling, and differences in sociodemographic factors. [4][5][6][7][8][9][10][11][12][13][14][15] Factors associated with increasing risk of seropositivity include ethnicity (indigenous or Afro-descent), presence of COVID-19 symptoms, past history of COVID-19 or close contacts, lower educational level, and working night shifts (for HCW) or in a prison. [4][5][6][7][8][9][10][11][12][13][14][15] Among these studies, a cross-sectional study in 2020 of 3,124 children aged 5 to 17 years in 10 Colombian cities reported highly variable seroprevalence ranging from 25.0% in Medellin to 63.9% in Guapi, the latter a coastal city with a high proportion of Afro-Colombians with the poorest living conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation